1981
DOI: 10.1007/bf00405069
|View full text |Cite
|
Sign up to set email alerts
|

Marker profiles of human leukemia and lymphoma cell lines

Abstract: By means of the multiple marker analysis, a total of 55 human leukemia-lymphoma cell lines which included 15 T-cell, 30 B-cell, four myelomonocytic-cell, and six non-T, non-B cell lines was characterized for their marker profiles. The multiple markers used included a number of cell surface markers as detected by either rosette or immunofluorescence tests, enzyme assays, cytogenetic analysis, and certain functional assay. Based on the criteria previously defined it was found that all the cell lines were proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…Human non-T ALL cell lines Reh and Nalm 12 (11) were kindly provided by Dr. P. Ralph of the Memorial Sloan-Kettering Cancer Center. Cell line Josh-7 was derived from a patient with X-linked agammaglobulinemia (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human non-T ALL cell lines Reh and Nalm 12 (11) were kindly provided by Dr. P. Ralph of the Memorial Sloan-Kettering Cancer Center. Cell line Josh-7 was derived from a patient with X-linked agammaglobulinemia (12).…”
Section: Methodsmentioning
confidence: 99%
“…By immunofluorescence, Josh 7 and Reh did not make any Ig whereas Nalm 12 made only cytoplasmic t~ chains. These cell lines represent human precursor and pre-B cell lines (11,12). Immunofluorescence studies as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The pre-B (CD19+ CD10 + Cm + /sIg À ) cell line NALM-6 and early B-cell/Burkitt's leukemia cell lines RAMOS, RAJI and DAUDI (CD19+sIgM+) (Uckun et al, 1991) were used in this study. The establishment, characterization and maintenance of these cell lines have been previously described in detail (Minowada et al, 1981). The leukemic T cell lines used in this study include, HuT 78 (Gootenberg et al, 1981), its clonal derivative H9 and Molt-3.…”
Section: Cell Lines and Patientsmentioning
confidence: 99%
“…Indeed, certain lymphomas and certain leukemias such as chronic lymphatic leukemia are now considered by Berard et al (19) "simply to represent different clinical expressions of the same neoplastic process." Further, recent immunologic (20) …”
Section: Discussionmentioning
confidence: 99%